Examining the role of constrained occupational mobility in the experience of entrapment cognitions. (30th May 2019) - Lim, Keith; Crane, Monique F.; Kansakar, David
Abstract : Objective: Entrapment cognitions play a significant role in the experience of mental ill‐health. Yet, no studies have investigated the emergence of entrapment in the occupational setting. In this article, we consider the indirect relationship of age and income to entrapment cognitions via perceived occupational mobility. Occupational mobility is the perceived ease of transition between occupations or professional groups. We examine whether constraints to occupational mobility may in fact increase entrapment cognitions among those employees with the desire to transition between occupations. Method: A cross‐sectional study was conducted with a sample of 180 Australian employees ( M age = 33.01; 21.10% males and 77.20% females) from a range of occupational settings. Measures were age, income, occupational mobility (non‐specific, age‐related, and income‐related), and entrapment cognitions. Results: The findings support the effect of increased age in reducing perceptions of occupational mobility (non‐specific and age‐related) and in turn increasing entrapment cognitions. Moreover, these mediating relationships were conditional on strong intentions to leave one's occupation. The same mediation effect did not emerge for income. Conclusions: This is the first study to examine the relationship between age, income, and entrapment cognitions via occupational mobility. Importantly, entrapment cognitions emerging from constrained occupational mobility may explain, in part, why certain occupational groups have a greater prevalence of mental health concerns than other groups. This study suggests a need to explore occupational mobility, and factors that constrain mobility, as possible precipitates of occupation‐related mental health concerns.